Tumor Necrosis Factor‐α‐Induced Protein‐8 Like‐2 (TIPE2) Upregulates p27 to Decrease Gastic Cancer Cell Proliferation. Issue 6 (June 2015) - Zhao, Qian; Zhao, Min; Dong, Tianyi; Zhou, Chengjun; Peng, Yanping; Zhou, Xiangyu; Fan, Bingbing; Ma, Wenzheng; Han, Mingyong; Liu, Shili
ABSTRACT The pathogenesis of gastric cancer is not completely understood. Tumor necrosis factor‐α‐induced protein‐8 like‐2 (TIPE2) has recently been identified as a novel negative regulator gene of the immune system, and studies in mice and humans have suggested its inhibitory action in both inflammation and cancer. In this study, we examined the expression levels of TIPE2 in human gastric cancer tissues and also samples of paraneoplastic control tissue, and found that TIPE2 expression was reduced in gastric cancer. To investigate the role of TIPE2 in gastric cell carcinogenesis, a TIPE2 plasmid was introduced into gastric cell lines and TIPE2 function was examined. Colony‐forming assays showed that restoration of TIPE2 expression in gastric cells significantly suppressed cell proliferation. Analysis by flow cytometry showed that the number of cells in the S phase of the cell cycle was reduced concomitant with TIPE2 expression, and cell apoptosis was maintained at a low level. Microarray and western blot analyses revealed that TIPE2 selectively up‐regulated N‐ras and p27 expression. The role of p27 in mediating TIPE2‐associated cell growth inhibition was verified by a p27 siRNA interference assay. In this study, we proved that TIPE2 is an inhibitor of gastric cancer cell growth, and suggest that TIPE2 might promote a p27‐associated signaling cascade that leads to restored control of the cell cycle and cell division. Our results provide a new molecular mechanism by which TIPE2 may regulate proliferation of gastric cells. J. Cell. Biochem. 116: 1121–1129, 2015. © 2015 Wiley Periodicals, Inc.